Electric vehicles charging station configuration with closed loop control - Wisam Mohamed Najem; Omar Sh. Alyozbaky; Shaker M. Khudher (Institute of Advanced Engineering and Science, 2023)
Recently, the demand for electric vehicles (EV) has been on the rise in global markets due to the orientation of national policies to reduce emissions and global warming through the electrification of the transportation sector and the use of clean energy sources. Electric vehicles function on batteries, which must be recharged, either by slow charging at home or by fast charging with a direct current. In the fast-charging process, the batteries can be charged in less than 15 minutes. In this paper, an off-board charger with a three-phase, six-pulse voltage rectifier was designed using the MATLAB/Simulink program. The closed control circuit was simulated, where the simulation results were influenced by changes to the input voltage. When the input voltage was increased or decreased by 5%, this control maintained the value of the current and voltage at the output to be equal to the reference values required to achieve fast charging. The simulation results showed that in the first case where no filter was used, the output voltage and current had a high amount of ripple that exceeded the permissible value. Therefore, a low-pass filter was designed to reduce the ripple factor to a value that was within the permissible limit.